A Spyware Platform and Predictive Models for Monitoring Computers - Darlan Noetzold; Anubis Graciela de Moraes Rossetto; Valderi Leithardt (Elsevier SSRN, 2025)
Noetzold, Darlan and Rosseto, Anubis and Leithardt, Valderi, A Spyware Platform and Predictive Models for Monitoring Computers (January 09, 2025). This paper is submitted in Elsevier Array., Available at SSRN: https://ssrn.com/abstract=5091771 or http://dx.doi.org/10.2139/ssrn.5091771